ZAKAT SEBAGAI PENGURANG PAJAK DAN PENGARUHNYA TERHADAP PENERIMAAN PAJAK DI SEMENANJUNG MALAYSIA - Eko Suprayitno; Radiah Abdul Kader; Azhar Harun (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This paper attempts to examine the role of zakat administration policy in Malaysia and its impact on the tax revenue in Malaysia Peninsula. Zakat administration issues pertaining to Islamic law but traditions remain under the jurisdiction of states. The practice of zakat is based on the Shariah while the taxation practice is based on the Malaysian Income Tax Act, established in 1967. Zakat is used as a fiscal policy tool whereby income tax payers were given 100 per cent rebates on zakat that they paid. The study uses panel data of states in Malaysia Peninsula and the analysis is done by using the fixed effect model. The study finds that zakat has a positif impact and significant on tax revenue.